2004
DOI: 10.1186/cc2889
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction N-terminal pro brain natriuretic peptide (NT-proBNP) is a cardiac biomarker that has recently shown to be of diagnostic value in a diagnosis of decompensated heart failure, acute coronary syndromes and other conditions resulting in myocardial stretch. We sought to study whether sepsisinduced myocardial dilation would result in an elevation of NT-proBNP. Method Serum NT-proBNP measurements were made in six consecutive patients with septic shock within 6 hours of admission to the intensive care unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…An understanding of the intimate relationships of the innate immune system, cytokines, pathogen-associated molecular pattern compounds, glucocorticoids, and B-type natriuretic peptides may serve in the future as a clinically useful paradigm to alert physicians to the possibility of impeding fulminating septic shock. [46][47][48][49]…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of the intimate relationships of the innate immune system, cytokines, pathogen-associated molecular pattern compounds, glucocorticoids, and B-type natriuretic peptides may serve in the future as a clinically useful paradigm to alert physicians to the possibility of impeding fulminating septic shock. [46][47][48][49]…”
Section: Discussionmentioning
confidence: 99%
“…It is produced in the prohormone form, and before secretion is split into the inactive NT-proBNP and the active BNP [ 36 ]. Numerous studies demonstrated markedly elevated plasma levels of BNP and NT-proBNP in septic patients [ 37 , 38 ], and the increased plasma BNP and NT-proBNP concentrations were associated with myocardial depression and increased mortality in patients with sepsis [ 39 , 40 ]. These findings suggest that plasma BNP and NT-proBNP levels represent reliable markers for the identification of SIMD.…”
Section: Biomarkers Of Simdmentioning
confidence: 99%
“…Several reports have indicated that plasma ANF or BNP levels are increased in sepsis and in septic shock patients [6164]. The increase in plasma NPs is partly due to cardiac dysfunction because plasma ANF or BNP was inversely correlated with cardiac function [6567].…”
Section: Bnp In Sepsis and Following Lps Treatmentmentioning
confidence: 99%